NUMERICAL MODELS OF THE ONSET OF YIELD STRENGTH IN CRYSTAL-MELT SUSPENSIONS - Saar M.O.; Manga M.; Cashman K.V.; Fremouw S. (My University, 2001)
The formation of a continuous crystal network in magmas and lavas can provide finite yield strength, τy, and can thus cause a change from Newtonian to Bingham rheology. The rheology of crystal-melt suspensions affects geological processes, such as ascent of magma through volcanic conduits, flow of lava across the Earth's surface, melt extraction from crystal mushes under compression, convection in magmatic bodies, and shear wave propagation through partial melting zones. Here, three-dimensional numerical models are used to investigate the onset of 'static' yield strength in a zero-shear environment. Crystals are positioned randomly in space and can be approximated as convex polyhedra of any shape, size and orientation. We determine the critical crystal volume fraction, φc, at which a crystal network first forms. The value of φc is a function of object shape and orientation distribution, and decreases with increasing randomness in object orientation and increasing shape anisotropy. For example, while parallel-aligned convex objects yield φc=0.29, randomly oriented cubes exhibit a maximum φc of 0.22. Approximations of plagioclase crystals as randomly oriented elongated and flattened prisms (tablets) with aspect ratios between 1:4:16 and 1:1:2 yield 0.08<φc<0.20, respectively. The dependence of φc on particle orientation implies that the flow regime and resulting particle ordering may affect the onset of yield strength. φc in zero-shear environments is a lower bound for φc. Finally the average total excluded volume is used, within its limitation of being a 'quasi-invariant', to develop a scaling relation between τy and φ for suspensions of different particle shapes.
Keywords: YIELD STRENGTH; CRYSTALS; LAVA FLOWS; FLOW MECHANISM; RHEOLOGY; MAGMAS